Anti-Rituximab Antibodies Occurrence and Clinical Outcomes in Patients With Primary Membranous Nephropathy - Marco Allinovi; Maxime Teisseyre; Matteo Accinno; Cecilia Finocchi; Vincent L.M. Esnault; Marion Cremoni; Tommaso Mazzierli; Daniela Lazzarini; Micaela Anna Casiraghi; Céline Fernandez; Kévin Zorzi; Vesna Brglez; et al. (Kidney International Reports, 2025)
Introduction: Rituximab is a first-line treatment for primary membranous nephropathy (pMN), with proven efficacy and safety. The use of monoclonal antibodies such as rituximab can lead to the formation of antidrug antibodies that may interfere with the therapeutic response. In pMN, anti-rituximab antibodies (ARAs) have been shown to neutralize the cytotoxicity of rituximab, thereby increasing the risk of relapse of nephrotic syndrome. However, the kinetics of ARAs over time and the effect of ARA titer on prognosis are unclear. Methods: This retrospective international multicenter study included 74 patients with pMN treated with rituximab. Here we aimed to clarify the correlation between ARAs and clinical outcome, as well as to evaluate the most appropriate timing of ARA detection. Results: Overall, 35 out of 74 patients (47%) developed ARAs after a median of 9 (interquartile range: 6–12) months following rituximab administration. ARA monitoring at month-9, month-12 and before rituximab readministration identified 88% of patients with ARAs. Clinical remission rate at 6 and 12 months after rituximab administration was significantly lower in patients with ARAs (31% vs. 56%, P = 0.03 and 54% vs. 87%, P = 0.0017, respectively). ARAs were associated with a significantly higher rate of relapse (63% vs. 29%, P = 0.036) and a higher rate of B-cell reconstitution at 6 months (74.2% vs. 50%, P = 0.048). Notably, relapse occurred earlier in patients with ARAs (22 months vs. 32 months, P = 0.01). Conclusion: The development of ARAs represents one of the most important prognostic factors in pMN, being significantly associated with a reduced remission rate and a higher relapse rate after rituximab therapy. Alternative therapies with obinutuzumab or ofatumumab should be considered for these patients.